A quality improvement project to reduce overutilization of blood tests in a teaching hospital - Mohammad Almeqdadi; Hari Krishnan Nair; Jeoffrey Hill; Julian Sanchez-Cruz; Claudia Nader; Bertrand L. Jaber (Greater Baltimore Medical Center, 2019)
Objective: In hospitals, physicians-in-training are major contributors to the burden of tests ordered, increasing cost and resource utilization. We implemented an intervention to discourage overutilization of the complete blood count (CBC) and the basic metabolic panel (BMP). Methods: An intervention was designed, comprising education on high-value care and burden of over-testing, encouragement of competition, and use of positive reinforcement. The intervention was monitored by a test index determined by dividing the total number of a specific laboratory test ordered for a patient by the total number of hospital days. Results: Following a 6-month intervention, the mean CBC index decreased from 1.56 ± 0.02 to 1.45 ± 0.03 (p < 0.001), and the BMP index, from 1.35 ± 0.02 to 1.14 ± 0.03 (p < 0.001). There was significant interaction between the intervention and the slope of the BMP index trend (p = 0.03), but not the CBC index trend. The intervention had no impact on hospital length of stay and mortality. Conclusion: This quality improvement intervention is an effective approach to reducing overutilization of laboratory tests.